Wild-caught fish populations targeted by MSC-certified fisheries have higher relative abundance than non-MSC populations - Melnychuk, Michael C.; Veneziano, Alessio; Lees, Samantha; Rasal, Jennifer; Koerner, Lauren M.; Hair, Peter; Costalago, David; Hively, Daniel; Jardim, Ernesto; Longo, Catherine (Frontiers in Marine Science, 2022)
Requirements for a fishery to achieve Marine Stewardship Council (MSC) certification include demonstrating that targeted populations (‘MSC stocks’) are fished at sustainable levels. The credibility of this claim can be evaluated by comparing estimated abundance of MSC stocks to benchmarks based on sustainability criteria. Additionally, to evaluate whether MSC certification provides a meaningful distinction, the sustainability status of MSC stocks can be compared with that of populations without a linked certificate (‘non-MSC stocks’). It is expected that MSC stocks are more likely to be maintained at levels of high abundance relative to sustainability benchmarks compared to non-MSC stocks. Similarly, it is expected that MSC stocks are less likely to become overfished, and if they do become overfished, that fisheries are incentivised to aid in their rebuilding to avoid suspension of certification. We compare published biomass estimates relative to biological reference points between MSC stocks and non-MSC stocks of wild-caught marine fish and invertebrate species around the world while controlling for the propensity of certification. Individual stocks from both groups were highly variable in relative biomass trends over the past two decades, with substantial overlap in the distributions of MSC and non-MSC stocks. In recent years (2014-2018), MSC stocks had, on average, greater biomass relative to biomass at maximum sustainable yield (BMSY) than non-MSC stocks. MSC stocks were also less frequently overfished compared to non-MSC stocks, with estimated biomass below a limit reference point (Blim) for 9% of MSC stocks and for 26-33% of non-MSC stocks. Eight MSC stocks currently or previously certified and defined as overfished in 2017 or 2018 had previously entered the program based on scientific advice available at the time indicating they were fished within sustainable limits. Subsequently, when revised stock assessments estimated the biomass to be lower than previously thought, fisheries for those stocks were suspended from certification. Together, these results suggest that eco-certification is associated with a credible claim on sustainable stock status and provides a useful distinction from other seafood. Further, our results show how the rare exceptions to this pattern may arise from retrospective changes in scientific advice.